1993
DOI: 10.1161/01.cir.87.6.1866
|View full text |Cite
|
Sign up to set email alerts
|

The long QT syndrome in children. An international study of 287 patients.

Abstract: The appearance of 2:1 atrioventricular block, multiform premature ventricular contractions, and torsade de pointes are relatively more common in children with LQTS than other children and should raise the index of suspicion for LQTS. Because 9% of patients presented with cardiac arrest and no preceding symptoms, perhaps prophylactic treatment in asymptomatic children is indicated. Asymptomatic patients with normal QTc and positive family history may be a low-risk group. Patients with QTc of more than 0.60 are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
152
0
13

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(169 citation statements)
references
References 14 publications
4
152
0
13
Order By: Relevance
“…By comparison, in the multi-institutional study by Garson et al (15), 45% of their patients presented with "serious" symptoms (sudden cardiac arrest, syncope, seizures). With a mortality of 9%, the Garson et al (15) study clearly describes a higher risk cohort than the LQTS athletes in this series.…”
Section: Discussionmentioning
confidence: 91%
“…By comparison, in the multi-institutional study by Garson et al (15), 45% of their patients presented with "serious" symptoms (sudden cardiac arrest, syncope, seizures). With a mortality of 9%, the Garson et al (15) study clearly describes a higher risk cohort than the LQTS athletes in this series.…”
Section: Discussionmentioning
confidence: 91%
“…7 Unfortunately, many of these patients are completely unaware of their condition, and sudden death can be the presenting symptom that leads to diagnosis. 8 In a recent retrospective review of pediatric patients with prolonged QT syndrome, only 17% of cases identified through family screening had experienced any symptoms prior to being diagnosed. 9 With this in mind, it may be prudent to inquire about a family history of serious dysrhythmias during the routine pre-anesthetic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…An ECG would be a simple and relatively inexpensive test to perform in individuals with a positive family history, although the resting ECG may still be normal in some individuals with prolonged QT syndrome. 8,10 Unfortunately, a negative family history is an insensitive screening tool for ruling out this condition. 8 It is well known that individuals with normal cardiac ion channels can also acquire a prolonged QT interval, usually as a consequence of consuming one or more of a host of QT-prolonging medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LQT 4, 5 and 6 all involve defects in potassium transmission, are located on chromosomes 4, 21 and 21, respectively, and are quite rare. All the genetic subtypes are characterized by a corrected QT interval of at least 440 msec on the 4 There have been numerous articles over the past 20 years describing isolated instances of surgical and anesthesia related complications but the general anesthetic management of the condition remains unclear. We present the case of an 11-yr-old child presenting for emergency surgery requiring general anesthesia, who suffered ventricular tachycardia during surgery.…”
Section: Objectif : Le Syndrome Congénital Du Qt Long Est Caractérisémentioning
confidence: 99%